Daratumumab induces CD38 internalization and impairs myeloma cell adhesion. (3rd October 2018) - Ghose, Jayeeta; Viola, Domenico; Terrazas, Cesar; Caserta, Enrico; Troadec, Estelle; Khalife, Jihane; Gunes, Emine Gulsen; Sanchez, James; McDonald, Tinisha; Marcucci, Guido; Kaur, Balveen; Rosenzweig, Michael; et al.
ABSTRACT: Daratumumab (Dara), a human immunoglobulin G1 kappa (IgG1κ) monoclonal anti-CD38 antibody, has been approved by the U.S. Food and Drug Administration for the treatment of relapsed multiple myeloma (MM) as a single agent as well as in combination with immunomodulatory drugs (IMiDs) and proteasome inhibitors (PI). Although the scientific rationale behind the use of Dara in combination with IMiDs has been extensively explored, the molecular mechanisms underlying Dara-PI regimens have not yet been investigated. Here, we demonstrate that CD38 on the surface of MM cells is rapidly internalized after Dara treatment; we also show that Dara treatment impairs MM cell adhesion, an effect that can be rescued by using the endocytosis inhibitor Dynasore. Finally, we show that Dara potentiates bortezomib (BTZ) killing of MM cells in vitro and in vivo, independent of its function as an immune activator. In conclusion, our data show that Dara impairs MM cell adhesion, which results in an increased sensitivity of MM to proteasome inhibition.